Depressıon and Communıty Mental Health (Turkey Health Literacy Journal, 2021)
Depression is a health problem that affects adversely human life both mentally and physically, causing deterioration of interpersonal harmony, professional and economic losses, decreased quality of life, and even suicide. It is common in the world and our country. Many different factors from biological reasons to psychosocial factors play a role in its etiology. When properly diagnosed and treated, its negative effects on the person and society can be prevented. In this review, the definition, etiology, epidemiology of depression, perspective on depression in terms of community mental health, and community mental health services are mentioned.